Development of control and audit systems in the context of population aging: integration of risk management, socio-economic imperatives and adaptation strategies - Shum, Alina (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2025)
The article examines modern systems of internal control and audit in enterprises in the context of population aging. The research object covers corporate governance mechanisms, risk management, and internal audit, all of which play a key role in ensuring organizational resilience amid demographic changes. Special attention is given to the specific risks associated with age-related structural changes in personnel and their impact on management effectiveness.Problem statement. The main problem lies in the fact that traditional systems of control and audit often prove inadequately adapted to new demographic challenges such as an aging workforce, which introduces cognitive, motivational, technological, and succession risks. This necessitates a revision of existing risk management and control approaches.Unresolved aspects of the problem. Open questions remain regarding the integration of the demographic factor into risk management systems, as well as the development of adaptive internal control and audit mechanisms that would ensure flexibility and effectiveness amidst changes in the age structure of personnel.Purpose of the article. The purpose of the article is to analyze the development of internal control, audit, and risk management systems in the context of population aging, as well as to identify ways to optimize these systems in order to improve the efficiency of enterprise management.Presentation of the main material. The paper systematizes four major categories of risks inherent to aging personnel: cognitive, technological, succession, and motivational. Functional differences between internal control, risk management, and internal audit subsystems are described. The stages of the risk management process and the roles of governance bodies at each stage are outlined, as are European trends concerning the socio-economic challenges of population aging.Conclusions. The research substantiates the feasibility of adapting control systems to demographic shifts, which can increase economic efficiency, reduce operational risks and costs, and improve employee satisfaction. Strategies for integrating risk management into corporate governance practice are proposed to prevent the negative consequences of age-related personnel changes.